2006
DOI: 10.1002/dc.20516
|View full text |Cite
|
Sign up to set email alerts
|

Role of different etiological factors in progression of cervical intraepithelial neoplasia

Abstract: Implication of high risk-human Papillomavirus in the process of cervical carcinogenesis is well documented. However, carcinogenesis in the cervix is recognized as multifactorial and other unknown etiological factors are also presumed to contribute to development of cancer. The present communication was aimed to investigate the role of risk factors such as age, parity, cervical lesions, and gynecological symptoms in the progression of the intra-epithelial cervical neoplasia. The study followed 571 cytologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 2 publications
2
12
0
1
Order By: Relevance
“…It is conceivable that if lesions were less likely to progress in younger versus older women then targeting older women would be justified or vice versa. Prospective studies in HIV-negative women have had inconsistent results: while lesions were more likely to progress in older women in some studies [23] the majority of studies noted similar progression rates irrespective of age [24-28]. Similar studies need to be conducted in HIV-positive women with limited access to systematic screening.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that if lesions were less likely to progress in younger versus older women then targeting older women would be justified or vice versa. Prospective studies in HIV-negative women have had inconsistent results: while lesions were more likely to progress in older women in some studies [23] the majority of studies noted similar progression rates irrespective of age [24-28]. Similar studies need to be conducted in HIV-positive women with limited access to systematic screening.…”
Section: Discussionmentioning
confidence: 99%
“…We know that the intraepithelial neoplastic lesions of the uterine cervix are multifactorial in their pathogenesis. [24] We also know that HPV is the primary etiologic agent leading to malign transformation of the epithelial cells. Yet, the manner in which the latent infection progresses to CC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers involved in this study suggested treating mild cervical lesions and persistent vaginal discharge to avoid or reduce the rate of progression to CIN. 10 …”
Section: Dasarimentioning
confidence: 97%